Enhancing Rural Entrepreneurship: Business Incubation and MSME Development in West Java - Khintan Evia Tulsi (Utan Kayu Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic growth, contributing significantly to GDP and employment. Despite their potential, MSMEs in rural West Java face challenges such as limited market access, inadequate entrepreneurial capacity, and insufficient infrastructure. This study examines the rural entrepreneurial ecosystem and proposes a business incubation model focused on stimulation, support, and sustainability to enhance MSME growth. Using a qualitative approach, data were collected through interviews with MSME operators, Village-Owned Enterprise (BUMDes) managers, and local government representatives. Thematic analysis identified key barriers, including a subsistence-oriented mindset, limited financial access, and weak institutional support. To address these challenges, this research proposes a tailored business incubation framework emphasizing entrepreneurial mindset development, mentorship, financial literacy, and infrastructure support. The model also integrates strategies for innovation, market expansion, and stakeholder collaboration. This study contributes to understanding rural entrepreneurial ecosystems and provides practical recommendations for policymakers and stakeholders to support sustainable MSME development in West Java.